Flexural and shear strengthening of RC beams with composites materials : the influence of cutting steel stirrups to install CFRP strips - Costa, Inês (2010)
Experimental, numerical and analytical investigations have revealed that Carbon Fibre Reinforced Polymer (CFRP) strips with larger cross section height improve the effectiveness of the Near Surface Mounted (NSM) technique for the flexural strengthening of existing reinforced concrete (RC) beams. However, this height is limited to the concrete cover thickness of the longitudinal steel bars, since the application of strips of cross section height larger than the cover thickness requires that the bottom arm of the steel stirrups be cut. This work aims to assess the influence, in terms of shear resistance, of cutting the bottom arm of steel stirrups to install NSM strips for the flexural strengthening of RC beams. The obtained results showed that, for monotonic loading, cutting the bottom arm of steel stirrups led to a decrease of the beam’s load carrying capacity of less than 10%. Due to the high effectiveness of the adopted NSM flexural strengthening systems, shear can be a predominant failure mode for these beams. To avoid this type of failure mode, strips of wet lay-up CFRP sheets with U configuration were used, resulting in effective strengthening solutions for RC beams. In the present paper the experimental program is described, and the obtained results are presented and discussed.